On the Theory of Convolution Integral Equations Related to Lebedev’s Type Operators - Yakubovich, Semyon B. (Sarajevo Journal of Mathematics, 2024)
We draw a parallel with the Gakhov-Cherskii method to investigate a class of convolution integral equations related to the Kontorovich-Lebedev and Lebedev's type transformations. A relationship with the Cauchy type integral is obtained. The general convolution equation is solved being reduced to the Riemann boundary value problem by means of the Kontorovich-Lebedev transform. 2000 Mathematics Subject Classification. 45A05, 45E05, 44A15, 33C10, 30E20, 30E25